Effect of pile arrangement on long-term settlement and load distribution in piled raft foundation models supported by jacked-in piles in saturated clay - Lua Thi Hoang; Xi Xiong; Tatsunori Matsumoto (Soils and Foundations, 2024)
When designing a piled raft foundation (PRF) on clay, it is essential to understand the time-dependent behaviors of the foundation. However, little attention has been paid to this issue. On the basis of physical model tests, this study presents the long-term behaviors of piled raft foundations with different pile arrangement schemes. In the experiments, three foundation models with the same square raft but different numbers of piles were tested to observe long-term foundation behavior under different vertical load levels. During the observation time, the applied load, the PRF settlement, the axial forces along the piles, and the pore water pressure (PWP) beneath the raft base were carefully measured. The results show that the piles were effective at supporting the applied load and suppressing the settlement of the foundation when the applied loads were smaller than the bearing capacities of the corresponding pile groups. At the larger loads, the raft shared significant proportions of the increment parts of the applied load. The level of the applied load affected the load sharing not only between the raft and the piles, but also between the piles. The corner piles carried larger load at small applied loads but smaller load at larger applied loads, in comparison with the center piles. In addition, due to the variations in load sharing between the raft and the piles, the pile arrangement and the level of applied load affected the distributions of ground strength in both the magnitude and the depth of the affected zone in long-term load tests.